STUDI EFEKTIVITAS PEMBELAJARAN SISTEM BLOK PADA MATA PELAJARAN PRODUKTIF TEKNIK PEMESINAN - Diya Zalfa Aisyah Safitri; Denny Aji Firmanta; Frendy Nur Setyawan; Garindo Prayitno; Hendri Aldi Puswadi; Ilham Agum Fitra Anggesa; Chandra Denny Kurniawan Putra; Suharno Suharno (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
This study evaluates the effectiveness of the block system learning in the productive subject of Machining Engineering at SMK Negeri 5 Surakarta. Utilizing a qualitative approach, the research findings indicate that the implementation of the block system enhances student engagement, deepens theoretical understanding, and improves practical skills. Interview analyses and case studies highlight a shift from a teacher-centered to a more participatory learning approach. Positive implications of constructivist and competency-based learning are evident in the enhanced quality of learning outcomes. The conclusion emphasizes the effectiveness of the block system learning as a relevant vocational education model aligned with industry needs. Recommendations include the development of teaching methods, increased industry involvement, and further research. Gratitude is extended to SMK Negeri 5 Surakarta, educators, students, and supporters who contributed to this research.